2017
DOI: 10.2147/ijnrd.s143186
|View full text |Cite
|
Sign up to set email alerts
|

The role of novel biomarkers in predicting diabetic nephropathy: a review

Abstract: Diabetic nephropathy (DN) is one of the microvascular complications of the kidney arising commonly from type 1 diabetes mellitus (T1DM), and occasionally from type 2 diabetes mellitus (T2DM). Microalbuminuria serves as an early indicator of DN risk and a predictor of its progression as well as cardiovascular disease risk in both T1DM and T2DM. Although microalbuminuria remains the gold standard for early detection of DN, it is not a sufficiently accurate predictor of DN risk due to some limitations. Thus, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 122 publications
(127 reference statements)
2
47
0
3
Order By: Relevance
“…During the course of DN, the functional derangement and structural remodeling of the kidney are considered to be triggered by hyperglycemic injury and linked to changes in several cellular events and activation of signaling pathways (Uwaezuoke, ). There is substantial evidence supporting that ROS is dramatically increased in kidney exposed to HG condition (Checherita et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During the course of DN, the functional derangement and structural remodeling of the kidney are considered to be triggered by hyperglycemic injury and linked to changes in several cellular events and activation of signaling pathways (Uwaezuoke, ). There is substantial evidence supporting that ROS is dramatically increased in kidney exposed to HG condition (Checherita et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yanyan Zhao et al identified two novel SNPs (rs10823108 in SIRT1 and rs17446614 in FOXO1) and two haplotypes within FOXO1 gene (defined by GT and GC) were susceptibility variants of DN and revealed SIRT1 and FOXO1 played a significant role in the development of DN in Chinese patients with type 2 diabetes (Zhao et al, ). Samuel N Uwaezuoke reported the role of novel biomarkers in predicting diabetic nephropathy, such as glomerular biomarkers, tubular biomarkers, biomarkers of inflammation, biomarkers of oxidative stress, and miscellaneous biomarkers, etc (Uwaezuoke, ). Patricia G Wilson et al demonstrated that renal apoB accumulation is conductive to the occurrence of DN and prevention of renal apoB accumulation by TGF‐β inhibition is protective against DN (Wilson, Thompson, Yoder, Charnigo, & Tannock, ).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made at classifying these biomarkers into major groups, although these groups overlap with one another. Representative groups include glomerular biomarkers; tubular biomarkers; biomarkers of inflammation; biomarkers of oxidative stress; and miscellaneous biomarkers [18]. Examples of each group of biomarkers include albumin, transferrin, laminin, immunoglobulin G, fibronectin, ceruloplasmin, type IV collagen, lipocalin-type prostaglandin synthase (L-PGDS), and glycosaminoglycans which make up the glomerular biomarkers; neutrophil gelatinase-associated lipocalin (NGAL), cystatin C, kidney molecule injury 1 (KIM-1), liver-type fatty acid binding protein (L-FABP), N-acetyl-β-D-glucosaminidase (NAG) and α-1-microglobulin constitute the tubular biomarkers; tumor necrosis factor-α (TNF-α), interleukin-1β, interleukin-8, interleukin-18, monocyte chemoattractant protein-1 (MCP-1), eotaxin, orosomucoid, RANTES and granulocyte colonystimulating factor (G-CSF) represent the biomarkers of inflammation; 8-oxo-7,8-dihydro-2-deoxyguanosine (8oHdG) is a typical example of a biomarker of oxidative stress; nephrin, podocalyxin, advanced glycation end products (AGEs), vascular endothelial growth factor (VEGF), heart fatty-acid binding protein (H-FABP) and retinol-binding protein are listed as miscellaneous biomarkers.…”
Section: Novel Biomarkers As Predictive Tools For Diabetic Nephropathymentioning
confidence: 99%